Chitosan-Based Hemostatic Pad Reduced Vascular Complications After Transradial Coronary Intervention in Uncontrolled Hypertensive Patients: Application of Chitosan-Based Hemostatic Pad on CAG or PCI - Lu Qian; Ming-Qiang Cao; Ze-Xiong Feng; Cao Zou; Si-Jia Sun; Sheng-Da Hu (Journal of Interventional Cardiology)
Conclusions: Chitosan-based HP treatment could reduce the incidence of vascular complications in patients with uncontrolled hypertension. Nonetheless, applying chitosan-based HP treatment after CAG or PCI procedures is not recommendable for controlled hypertensive patients.